Relationships reduce risks for child maltreatment: Results of an experimental trial of Infant Mental Health Home Visiting - Julian, Megan M.; Riggs, Jessica; Wong, Kristyn; Lawler, Jamie M.; Brophy-Herb, Holly E.; Ribaudo, Julie; Stacks, Ann; Jester, Jennifer M.; Pitzen, Jerrica; Rosenblum, Katherine L.; Muzik, Maria; , on behalf of The Michigan Collaborative for Infant Mental Health Research (MCIMHR) (Frontiers in Psychiatry, 2023)
Background: Research examining the effectiveness of home visiting programs that reduce child maltreatment or associated risks yield mixed findings; some find positive significant impacts on maltreatment, whereas others find small to no effects. The Michigan Model of Infant Mental Health Home Visiting (IMH-HV) is a manualized, needs-driven, relationship-focused, home-based intervention service that significantly impacts maternal and child outcomes; the effect of this intervention on child maltreatment has not been sufficiently evaluated. Objective: The current study examined associations between treatment and dosage of IMH-HV and child abuse potential in a longitudinal, randomized controlled trial (RCT). Participants and Setting: Participants included 66 mother-infant dyads (Mother M age=31.93 years at baseline; child M age=11.22 months at baseline) who received up to 1 year of IMH-HV treatment (Mdn=32 visits) or no IMH-HV treatment during the study period. Methods: Mothers completed a battery of assessments including the Brief Child Abuse Potential Inventory (BCAP) at baseline and at the 12-month follow-up assessment. Results: Regression analyses indicated that after controlling for baseline BCAP scores, those who received any IMH-HV treatment had lower 12-month BCAP scores compared to those who received no treatment. Additionally, participation in more visits was associated with lower child abuse potential at 12 months, and a reduced likelihood of scoring in the risk range. Conclusions: Findings suggest that greater participation in IMH-HV is associated with decreased risk for child maltreatment one year after initiating treatment. IMH-HV promotes parent-clinician therapeutic alliance and provides infant-parent psychotherapy which differentiate it from traditional home visiting programs.